Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1046/j.1468-2982.1994.1402171.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Headache in Migraine Without Aura and Episodic Tension-Type Headache in The Turkish Population According to the IHS Classification

Abstract: We evaluated the characteristics of headache in migraine without aura and episodic tension-type headache diagnosed according to the International Headache Society (IHS) Classification. Fifty migraine without aura and 50 tension-type headache patients were selected prospectively. Fifty-eight percent of migraineurs had pain of a pulsating quality; 88% had severe pain and 74% had unilateral pain; aggravation by routine physical activity was reported by 96%. Episodic tension-type headache was of a pressing quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 12 publications
4
11
1
Order By: Relevance
“…Aggravation by routine physical activity was reported to be in the ratio of 96% in the mentioned study. Our results (throbbing 96.6%, unilaterality 49.2% in patients with MWOA) are very different to this study (5), probably because of the difference between the study populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Aggravation by routine physical activity was reported to be in the ratio of 96% in the mentioned study. Our results (throbbing 96.6%, unilaterality 49.2% in patients with MWOA) are very different to this study (5), probably because of the difference between the study populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Migraine is commonly unilateral, pulsating, moderate to severe in intensity, and is associated with nausea, photophobia and phonophobia. In a previous study performed in migraine patients without aura appling to an university hospital in Turkey (5), 58% had pain of pulsating quality, 74% had unilateral pain. Aggravation by routine physical activity was reported to be in the ratio of 96% in the mentioned study.…”
Section: Discussionmentioning
confidence: 93%
“…Unilateral location had high Sp – 88%, but low Se – 27%. Low Se of this item in children and adolescents was also established in other studies (6,16,18,19,25,37), in contrast with higher Se (53–74%) in adults (21,38–40). That is why unilateral location was confirmed as diagnostic item in criterion C for migraine in adults in ICHD – II (23).…”
Section: Discussionsupporting
confidence: 72%
“…However, headache duration may also vary because of study designs as some studies reported durations with treatment and others without. In addition, as mentioned by Inan and colleagues, 22 one also has to consider that there are educational and cultural differences in the investigated populations, which may affect the individual description of headache duration and therefore make comparison difficult.…”
Section: Discussionmentioning
confidence: 99%